Evaluation of Core Stabilization Strenght of Team and Individual Athletes and Sedentary - Levent Ceylan, Özlem Yilmaz, Murat Eliöz, Faruk Albay, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: This study was carried out to examine the core strength of athletes and sedentary people between the ages of 13-18. Methods: 200 male athletes from Samsun and 51 sedentary men who did not do any sports participated in this study. The Plank Fitness Test was applied to measure core strength and the time they could stand without disturbing the plank position was recorded. IBM SPSS Statistics 21 package program was used in the analysis of the data. Before the analysis of the data, Shapiro-Wilk normality test was applied and it was determined that the data did not show normal distribution (p<0.05). The Kruskal-Wallis H test was used to compare the averages of core duration between the groups. Results: According to the findings obtained in the study, a significant difference was found when the durations of the groups in the core test were examined [X2(2) =92,158, p<.05]. This finding shows that the core strength between the groups is different according to the branch. When the averages of the groups are examined, it is determined that the branch with the highest core duration is judo (190.53 sec.), followed by taekwondo (158.18 sec.), football (158.01 sec.), sedentary (107.73 sec.) and basketball (69.55 sec.) groups, respectively. In addition, it is seen that the results obtained in core times and the results of training age and body mass index values are similar. Conclusion: According to the results of our study, it is noteworthy that those who do individual sports have higher core scores than those who do team sports and sedentary. We think that this difference is due to the fact that the concentration is constantly high in individual sports and the techniques performed accordingly require more core strength. In addition, we can say that the fact that sedentary people get more core points than basketball players is due to the fact that the training age of the participants and the body mass index values of the basketball players are higher than the other participants. In the light of these results, we think that more core training should be included, especially in sports that require high technical skills and strength.